Informal Workers’ Aggregation in India: An Evolving Model of Collective Action - Routh, Supriya (Sociologie et sociétés, 2015)
In India, more than 90 % of the workforce is informal. In spite of this enormous percentage of informal workers, informal workers remain excluded from law and policy circles. One reason for such exclusion and invisibility emanates from the absence of trade unionism involving informal workers. Overcoming this invisibility, informal workers are increasingly organizing into associations that differ from traditional trade unions. These organizations devise their strategies and their legal statuses in view of the atypical characteristics of informal activities. In this article, I document some of these organizations of self-employed informal workers in India. By documenting the characteristics and functions of these organizations, I contend that these organizations offer a model for collective action by informal workers. I argue that these associations of informal workers are a sui generis organization of informal workers, and could become a precursor to solidarity-based initiative by informal workers globally.